Participación de la interleuquina-10 en la inmunosupresión inducida por endotoxinas bacterianas - Córdoba Moreno, Marlina Olyissa (2017)
Septic processes constitute one of the major causes of death in intensive care. Even though sepsis presents a simultaneous induction of both, an inflammatory and anti-inflammatory agents (TNF-?, IL-1, IL-6, IL-8, IFN-?, IL-10, TGF-? y GC), in early phases predominates a characteristic clinical state of a hyper-inflammatory response, whereas during later phases an anti-inflammatory response becomes predominant. It is during this last state that more than 70% of sepsis deaths occur due to failure in controlling pathogens associated to an immunosuppression state. In sepsis caused by Gram-negative bacteria, endotoxins, a normal constituent of the bacterial outer wall, also known as lipopolysaccharide (LPS), has been considered one of the principal agents causing the undesirable effects in this critical illness.\nLike we previously demonstrated the glucocorticoids (GC) participation in this immunosuppression, the aim of this study was to evaluate the IL-10 contribution to it, as well as its potential relationship with glucocorticoids. For this, wild type (WT) and IL-10 deficient (IL-10 KO) BALB/c mice were immunosuppressed with LPS.\nResults shows that IL-10 KO mice were more sensitivity to LPS, probably due to an elevated and sustained level of principal proinflammatory cytokines associated to sepsis (TNF-?, IL-12 and IFN-?) and to the elevated number of TNF-? receptors observed in these mice with respect to WT mice. The levels of corticosterone were higher too, although dexamethasone did not protect of LPS lethal challenge (2LD50=200ug). The basal status of the primary humoral immune response -but not the secondary- and the level of IS were similar in both strains.\nAlthough IL-10 did not modify the humoral immune status nor changed the LPS-induced immunosuppression, is critical for controlling early production of TNF-? after LPS and the refractoriness induced by glucocorticoids.\nOur results support the thesis of a bidirectional regulation between GC and IL-10. However, while GC exerts a positive regulation on IL-10, a negative action of IL-10 was observed on GC levels.\nFinally, this work was an attempt of contributing to the knowledge about the mechanisms of immunosuppression that, eventually, can help to incorporate the implementation of therapeutic procedures in sepsis on a rational basis.